Using technology in human trafficking: international law perspective and reflections within Middle Eastern countries. (1st January 2015) - Khalaileh, Yaser; Kisswani, Nazzal
Human trafficking represents a serious violation of human rights, dignity and freedom. Many states have attempted to develop effective policies to combat human trafficking. The UN, as well as the European Union and the European Council, strived to develop policies and regulations in criminalising human trafficking, and have made a real progression in the judicial procedures needed to protect the victims of trafficking and in the process of rehabilitating them. The adoption of the Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially in Women and Children of 2000, is possibly one major cornerstone in this respect. This study aims at analysing the possible effectiveness of these contributions, and others, to include mainly the fact that human trafficking is now widely operated through the use of internet and other technology means. The extent of trusting the statistical information provided by states about human trafficking via the internet places a serious problem. Also, the limited scope of the rules of international law governing the issue of human trafficking via electronic means is just another problem. It is suggested that while there are obvious international law rules governing the crime of human trafficking in general, they nonetheless do not provide an integrated model for eliminating human trafficking via the internet, or even sufficiently hold the perpetrators of such crimes accountable for their crimes, and do not contain effective punitive measures.